Peripheral plasma adenosine release in patients with chronic heart failure. Issue 8 (27th November 2008) - Franceschi, F; Deharo, J-C; Giorgi, R; By, Y; Monserrat, C; Condo, J; Ibrahim, Z; Saadjian, A; Guieu, R
Abstract : Objective: Chronic heart failure (CHF) is accompanied by increased adenosine plasma levels (APLs). It is unknown whether adenosine release occurs at the peripheral level or whether the myocardium itself is the source of adenosine release. To answer this question, we evaluated APLs in the coronary sinus of CHF patients during a resynchronisation procedure and compared the values with those at the peripheral level. We also investigated a possible correlation between APLs and ischaemia-modified albumin (IMA) levels, a useful marker of tissue ischaemia. Methods: 19 men and seven women were prospectively included. Blood samples for APLs were collected simultaneously from a brachial vein (peripheral) and from the coronary sinus. Blood samples for brain natriutretic peptide (BNP) and IMA were collected from a brachial vein. Results: APLs from the brachial vein were higher than those from the coronary sinus (1.69 vs 0.75 μM p<0.01). IMA levels were correlated with APLs from the brachial vein (r = 0.59, p<0.01). BNP concentrations were correlated with APLs from the brachial vein (r = 0.73, p<0.001) but not with APLs from the coronary sinus (r = 0.38, p>0.05). BNP concentrations and IMA levels were correlated (r = 0.71, p<0.001). Conclusions: In CHF patients, adenosine release occurs at a peripheral level and not at the myocardium level.